2008
DOI: 10.2146/ajhp070112
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine: Treatment for substance abuse and drug of abuse

Abstract: Quetiapine is a promising treatment for substance use disorders alone or combined with other psychiatric diagnoses, such as bipolar disorder and schizophrenia. Quetiapine abuse has also been documented, particularly in the correctional setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…[47] Both quetiapine and olanzapine have acquired a street price in the US. [47,48] Of note, quetiapine has picked up a collection of street names including Susie-Q, Baby Heroin, Quell and Q-Ball. [46,49,50] …”
Section: Abuse Of Aapsmentioning
confidence: 99%
“…[47] Both quetiapine and olanzapine have acquired a street price in the US. [47,48] Of note, quetiapine has picked up a collection of street names including Susie-Q, Baby Heroin, Quell and Q-Ball. [46,49,50] …”
Section: Abuse Of Aapsmentioning
confidence: 99%
“…Interestingly, patients initiated on olanzapine and quetiapine, both multi-receptor targeted antipsychotics 35 , were more likely to have a history of drug abuse (6.8% for lurasidone versus 13.9% for olanzapine and 13.6% for quetiapine) than patients initiated on lurasidone. Previous research has also reported that quetiapine was more likely to be used by patients with comorbid substance use 36 and anecdotal evidence suggests that quetiapine may be used off-label to treat substance abuse 37 . Finally, patients treated with lurasidone in this study had a lower prior risk of hospitalization, an important potential marker of a more debilitating condition 30 .…”
Section: Discussionmentioning
confidence: 98%
“…Quetiapine is used to treat the symptoms of patients suffering from schizophrenia, bipolar disorder and major depressive disorder, under the trade name Seroquel ® (AstraZeneca) [5,6]. There is also evidence that quetiapine may benefit patients diagnosed with a mental illness who are also dependent on alcohol [7][8][9], cocaine [5,7,9], amphetamines [9,10], and for the reduction of opioid withdrawal symptoms [11]. Although, more rigorous studies are needed [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is surprising that quetiapine appears to be the primary if not the only one antipsychotic drug which is misused for this purpose [14,29]. Curiously, the drug accused of misuse/abuse is used as a treatment for those who misuse and abuse various substances, such as opioids, cocaine, and amphetamines or alcohol [1,5,[7][8][9][10][11]. It is discussed whether quetiapine works by improving comorbid psychiatric conditions of drug addicts or by directly reducing craving [27,30].…”
Section: Introductionmentioning
confidence: 99%